2010
DOI: 10.1128/jb.01553-09
|View full text |Cite
|
Sign up to set email alerts
|

The Abi Proteins and Their Involvement in Bacteriocin Self-Immunity

Abstract: The Abi protein family consists of putative membrane-bound metalloproteases. While they are involved in membrane anchoring of proteins in eukaryotes, little is known about their function in prokaryotes. In some known bacteriocin loci, Abi genes have been found downstream of bacteriocin structural genes (e.g., pln locus from Lactobacillus plantarum and sag locus from Streptococcus pyogenes), where they probably are involved in self-immunity. By modifying the profile hidden Markov model used to select Abi protei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
94
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 95 publications
(96 citation statements)
references
References 50 publications
1
94
1
Order By: Relevance
“…chymotrypsin cleavage at Tyr16 (Table S1). Proteolysis is an established mechanism of bacteriocin resistance and immunity [32].…”
Section: Discusssionmentioning
confidence: 99%
“…chymotrypsin cleavage at Tyr16 (Table S1). Proteolysis is an established mechanism of bacteriocin resistance and immunity [32].…”
Section: Discusssionmentioning
confidence: 99%
“…Members of the CPBP family are involved in diverse biological functions. For example, Kjos et al have shown that SkkI functions as a bacteriocin immunity protein for sakacin secreted by Lactobacillus plantarum (71). These authors have also shown that protease activity is necessary for the immunity function.…”
Section: Discussionmentioning
confidence: 99%
“…The mccF_like gene belongs to the Peptidase_S66 superfamily and encodes a microcin C7 self-immunity protein resistant to microcin C7 (MccF) [44]. The Abi _like protein belongs to the Abi family (also known as the CAAX prenyl protease family) consisting of putative membrane-bound metalloproteases [45]. In general, Abi is located downstream of bacteriocin structural genes, where it may be involved in selfimmunity [45].…”
Section: Eiicmentioning
confidence: 99%
“…The Abi _like protein belongs to the Abi family (also known as the CAAX prenyl protease family) consisting of putative membrane-bound metalloproteases [45]. In general, Abi is located downstream of bacteriocin structural genes, where it may be involved in selfimmunity [45]. Within PZ-II, a number of membranerelated proteins containing several transmembrane regions and a PadR family transcriptional regulator were identified upstream of mccF_like and Abi_like proteins.…”
Section: Eiicmentioning
confidence: 99%
See 1 more Smart Citation